CRISPR-Mediated Triple Knockout of SLAMF1, SLAMF5 and SLAMF6 Supports Positive Signaling Roles in NKT Cell Development. - Bonnie Huang; Julio Gomez-Rodriguez; Silvia Preite; Lisa J Garrett; Ursula L Harper; Pamela L Schwartzberg (PLoS ONE)
The SLAM family receptors contribute to diverse aspects of lymphocyte biology and signal via the small adaptor molecule SAP. Mutations affecting SAP lead to X-linked lymphoproliferative syndrome Type 1, a severe immunodysregulation characterized by fulminant mononucleosis, dysgammaglobulinemia, and lymphoproliferation/lymphomas. Patients and mice having mutations affecting SAP also lack germinal centers due to a defect in T:B cell interactions and are devoid of invariant NKT (iNKT) cells. However, which and how SLAM family members contribute to these phenotypes remains uncertain. Three SLAM family members: SLAMF1, SLAMF5 and SLAMF6, are highly expressed on T follicular helper cells and germinal center B cells. SLAMF1 and SLAMF6 are also implicated in iNKT development. Although individual receptor knockout mice have limited iNKT and germinal center phenotypes compared to SAP knockout mice, the generation of multi-receptor knockout mice has been challenging, due to the genomic linkage of the genes encoding SLAM family members. Here, we used Cas9/CRISPR-based mutagenesis to generate mutations simultaneously in Slamf1, Slamf5 and Slamf6. Genetic disruption of all three receptors in triple-knockout mice (TKO) did not grossly affect conventional T or B cell development and led to mild defects in germinal center formation post-immunization. However, the TKO worsened defects in iNKT cells development seen in SLAMF6 single gene-targeted mice, supporting data on positive signaling and potential redundancy between these receptors.